The Sage encyclopedia of qualitative research methods - Given, Lisa M. (SAGE, 2008)
The SAGE Encyclopedia of Qualitative Research Methods (two volumes) presents state-of-the-art information and ready-to-use techniques, facts, and examples from the field of qualitative methods in a non-intimidating and accessible style.